Investigation of Bladder Volume Measurement Based on Fringe Effect of Electrical Impedance Tomography Sensors - Liu, Kangqi; Bai, Xu; Wei, Jinzhao; Liang, Xiaofeng; Sun, Jiangtao; Xu, Lijun (IEEE open journal of instrumentation and measurement, 2022)
Patients with bladder dysfunction are unable to perceive bladder volume and urinate spontaneously, and hence usually require catheterization. Personalized catheterization can effectively reduce the risk of urinary tract infections caused by catheterization. Electrical impedance tomography (EIT) can provide an effective tool for personalized catheterization by monitoring bladder volume. This study exploits the fringe effect of a 2D EIT sensor to derive the 3D volumetric information about bladder and improve the measurement consistency and accuracy of bladder volume under varied urine conductivities. The EIT sensor is optimized regarding the specified application of fringe effect. The parameters to be optimized include the electrode arrangement, the distance of electrode plane from bladder bottom, and the number of electrodes. Three evaluation criteria are proposed for the optimization. Simulation and experiment confirm the feasibility of the fringe effect-based method for bladder volume measurement, and the performances of the optimized sensor are illustrated. It is concluded that the fringe effect-based method has a better measurement consistency and accuracy against urine conductivity than the widelyused global impedance-based method, and hence provides a new promising alternative for bladder volume measurement.